The effect of behavioral factors on investment decision towards stock market between Indonesia, Japan, and Thailand - Marciano, Deddy; Wijaya, Liliana Inggrit; Sugianto, Laurenco Lingguardi; Zunairoh, Zunairoh (Jurnal Siasat Bisnis, 2025)
Purpose – This research consists of Behavioral Finance where it is focused on cognitive bias factors influence on Investment Decision with using the scope of research in three countries which are Indonesia, Thailand, and Japan.Design/methodology/approach – the method of research is categorized as quantitative research where it uses a questionnaire with 232 respondents. Then, the data is processed and analyzed using software SmartPLS 3.0.Findings – The findings reveal that overconfidence and availability bias have a significant positive effect on investment decisions, while herding behavior has a negative effect and anchoring bias shows no significant influence.Research limitations/implications – This research is limited by its relatively small sample size of 232 respondents across three culturally and economically diverse countries, which may affect the generalizability of the findings.Practical implications – The strong influence of overconfidence and availability bias highlights the need for improved investor education focused on risk awareness and critical analysis, especially in the digital era. Also, to prevent irrational behavior driven by herding, financial institutions and regulators should enhance collective financial literacy and promote transparent, data-driven decision-making.Originality/value – This result provides reasonable insight into why there is a difference in results between each country supported with the data and results from the previous research that have been done before.